Weed species preferences by katjang goats in oil palm plantation - Zaki, Nurul Syahirah (2017)
Goats possess characteristics including versatility in grazing adverse plant species and the ability to survive under different foraging condition which put them apart from other livestock animals. Three female Katjang were used pastured under the plantation that contain variety of weed species. The objective is to establish the weed species preferences by goats in oil palm plantation. Specifically, the weeds preferences were determined by the reference of individual animal and grazing day. The weight gain of the goats were also recorded every week to show the progress of the goats. Grazing behavioral data that included number of bites and time spend on each weed species were recorded using the direct observation method and the measurements were performed every day for 28 days of period. According to the result, broadleaved weeds and grasses were the most selected by the goats. In the final analysis, Asystasia intrusa was the most preferred weeds species and shows that it was the most important part of the diet of goats in such ecosystem. In contrary, Ishaemum musticum was the last preferred based on the top 5 rankings could be largely explained by the fact that goats are naturally browsers.